2011
DOI: 10.1007/s00701-011-1017-2
|View full text |Cite
|
Sign up to set email alerts
|

A temporal pattern in the occurrence of aneurysmal subarachnoid hemorrhage in the Province of Vojvodina, Serbia

Abstract: The results are a clear confirmation that SAH patients do indeed present in clusters in a restricted population area. This exact clustering in our series is not particularly connected to month or season, yet strongly supports the existence of a temporal pattern in SAH occurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…Prior research has suggested that ambient temperature, precipitation, sunlight, average humidity, and the lunar cycle may all be associated with an increased risk of rupture of cerebral aneurysms [4] , [5] , [10] [13] . On the other hand, others have found no associations between weather patterns and subarachnoid hemorrhage [3] , [8] , [9] . One recent large meta-analysis review of the literature found SAH to be associated with the winter and January [14] .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Prior research has suggested that ambient temperature, precipitation, sunlight, average humidity, and the lunar cycle may all be associated with an increased risk of rupture of cerebral aneurysms [4] , [5] , [10] [13] . On the other hand, others have found no associations between weather patterns and subarachnoid hemorrhage [3] , [8] , [9] . One recent large meta-analysis review of the literature found SAH to be associated with the winter and January [14] .…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, associations between meteorological parameters and cerebral aneurysm rupture have also been observed to vary by sex [6] , [7] . However, the findings in the literature have been inconsistent: other studies have suggested that subarachnoid hemorrhage does not vary with season or temperature [8] , [9] .…”
Section: Introductionmentioning
confidence: 94%
“…Previous studies of different races yielded inconsistent results on the diurnal variation of aSAH [ 3 5 6 ]. Most of them were conducted in Western countries, and they lacked subgroup analyses of influencing factors such as age, gender, and hypertension [ 5 6 7 8 9 10 11 ]. The incidence of aSAH onset could be very different among people in distinct cultures for differential lifestyle habits.…”
Section: Introductionmentioning
confidence: 99%
“…Intracranial or brain aneurysms as dilation of the intracranial blood vessels usually manifest clinically in middle age at around 50 years [1,2]. The incidence of intracranial aneurysms in patients younger than 18 years of age is very low and the percentage is 1 to 2 of the total number of all aneurysms [3,4].…”
Section: Introductionmentioning
confidence: 99%